Hisbah and Its Real-World Applications in Islamic Banks: A Contemporary Qur’anic Maqasidic Study - Abu- Alhaj, Thabet Ahmad Abdullah; Norasid, Muhamad Alihanafiah; Al-Siyabi, Sami Mohamed Hamid (Journal of Cultural Analysis and Social Change, 2026)
This study explores the concept of Hisbah and its practical foundations within the framework of Islamic banking, through a contemporary Qur’anic and Maqasidic (objectives-based) perspective. It aims to demonstrate that Hisbah—as an institutionalized mechanism of moral and financial accountability—constitutes an essential component of Islamic governance systems. By analyzing Qur’anic principles and classical juristic sources, the research highlights how Hisbah embodies the higher objectives of Shariah, particularly the preservation of wealth (hifz al-mal) and the promotion of justice and transparency in economic activities. The study further examines the role of Hisbah in regulating Islamic financial institutions, ensuring compliance with Shariah principles, and strengthening ethical governance frameworks. Ultimately, the research proposes that integrating Hisbah into modern Islamic banking supervision can enhance institutional integrity and contribute to achieving sustainable development aligned with the Qur’anic Maqasid.